Comparison between concept-based and procedure-based in circle theorems - Dickson Edem Gadaglo; Clement Ayarebilla Ali (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: The debate between concept-based instruction and procedure-based approaches to improving students’ performance, understanding, and skill development in Circle Theorems cannot be over-emphasized. The researchers employed the non-equivalent quasi-experimental design to investigate the effectiveness and appropriateness of the two methods, using circle theorems.Aim: This study aims to compare the effectiveness of concept-based and procedure-based instructional approaches in the teaching of Circle Theorems among senior high school students.Method: A quasi-experimental design was adopted involving 70 students selected from two purposively sampled schools. One school was assigned as the experimental group (concept-based instruction) and the other as the control group (procedure-based instruction). Geometry achievement tests were administered as pre-tests and post-tests. Data were analyzed using paired sample t-tests, independent sample t-tests, and effect size calculations with a significance level set at 5%.Result: The findings showed statistically significant differences between the experimental and control groups. Students taught using concept-based instruction performed significantly better than those taught through procedure-based instruction. High effect sizes further supported the superiority of the concept-based approach.Conclusion: Concept-based instruction enhances students’ understanding and performance in Circle Theorems. It is recommended that mathematics educators adopt teaching methods that promote conceptual understanding and active knowledge construction over algorithmic procedures.